2012
DOI: 10.1098/rsob.120132
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule plus-ends within a mitotic cell are ‘moving platforms’ with anchoring, signalling and force-coupling roles

Abstract: The microtubule polymer grows and shrinks predominantly from one of its ends called the ‘plus-end’. Plus-end regulation during interphase is well understood. However, mitotic regulation of plus-ends is only beginning to be understood in mammalian cells. During mitosis, the plus-ends are tethered to specialized microtubule capture sites. At these sites, plus-end-binding proteins are loaded and unloaded in a regulated fashion. Proper tethering of plus-ends to specialized sites is important so that the microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 174 publications
(183 reference statements)
2
64
0
Order By: Relevance
“…Na V 1.5 is trafficked to and delivered into the cell membrane by the microtubule network. Specific sites of delivery are determined by macromolecular complexes composed of anchoring and microtubule capture proteins 19, 24. In TAC hearts, increased protein expression levels of the microtubule protein α‐tubulin and plus‐end microtubule capture protein EB1 were observed, indicating a denser microtubule network and a potential increase in microtubule capture sites at the cell membrane (Figure 8A and 8B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na V 1.5 is trafficked to and delivered into the cell membrane by the microtubule network. Specific sites of delivery are determined by macromolecular complexes composed of anchoring and microtubule capture proteins 19, 24. In TAC hearts, increased protein expression levels of the microtubule protein α‐tubulin and plus‐end microtubule capture protein EB1 were observed, indicating a denser microtubule network and a potential increase in microtubule capture sites at the cell membrane (Figure 8A and 8B).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we used superresolution localization microscopy (STORM) to resolve the molecular organization of Na V 1.5 in fixed cardiomyocytes isolated from Sham and TAC ventricles, with a lateral resolution of 20 nm 19, 24. No differences in Scn5a mRNA levels or total Na V 1.5 protein levels were observed between Sham and TAC ventricular tissue (Figure 9A through 9C).…”
Section: Resultsmentioning
confidence: 99%
“…End-binding proteins (þTIPs), such as EB1, interact with the plus ends of growing MTs, capture MTs at cortical sites to establish an asymmetric MT network, and regulate MT linkage to actin. 12,51 In epithelial cells, b-catenin at adherens junctions binds MT end-binding proteins to facilitate the delivery of junctional components, 52 which would be critical for BTB restructuring. EB1-decorated MTs were disorganized in Sertoli cells of the seminiferous tubules of AKAP9-deficient testes, and cultured Akap9 cko Sertoli cells lacked distinct EB1 comets, which in other cell systems reflect a change in MT dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…It was later demonstrated that a STIM1 sequence encompassing residues 642-645 (residues Thr-Arg-Ile-Pro, or TRIP) is critical for the binding to EB1 (Honnappa et al, 2009). A similar sequence (S/TxIP) is found in other +TIPs (Tamura and Draviam, 2012), and for some of these EB1 interactors, such as CLASP2 and APC, it was found that the phosphorylation of the +TIP regulates the association to EB1 (Kumar et al, 2009;Watanabe et al, 2009;Zumbrunn et al, 2001).…”
mentioning
confidence: 99%